2012
DOI: 10.3389/fmicb.2012.00109
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Iron Cycling in Acidic Geothermal Springs of Yellowstone National Park: Integrating Molecular Surveys, Geochemical Processes, and Isolation of Novel Fe-Active Microorganisms

Abstract: Geochemical, molecular, and physiological analyses of microbial isolates were combined to study the geomicrobiology of acidic iron oxide mats in Yellowstone National Park. Nineteen sampling locations from 11 geothermal springs were studied ranging in temperature from 53 to 88°C and pH 2.4 to 3.6. All iron oxide mats exhibited high diversity of crenarchaeal sequences from the Sulfolobales, Thermoproteales, and Desulfurococcales. The predominant Sulfolobales sequences were highly similar to Metallosphaera yellow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
119
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(125 citation statements)
references
References 32 publications
4
119
0
2
Order By: Relevance
“…and Hydrogenobaculum spp. (Aquificales), as well as other less abundant, uncharacterized archaea and bacteria (Kozubal et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…and Hydrogenobaculum spp. (Aquificales), as well as other less abundant, uncharacterized archaea and bacteria (Kozubal et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Contigs assigned to each replicate de novo assembly have similar G þ C content (%) and sequence read coverage that clearly distinguish them from other population clusters in this community (example shown in Supplementary Figure S1). Comparison of NAG1 sequence to reference databases (via blastp or blastn) revealed a consistent pattern (that is, poor sequence similarity to current reference genomes), and is clearly different than the other three to four predominant populations present in these systems (Kozubal et al, 2012). The assemblies were evaluated using NWF-PCA (Teeling et al, 2004), which showed that the sequence content and character (that is, G þ C content, codon usage) are nearly identical among the four NAG1 replicates, and that these assemblies differ significantly compared with four representative phyla within the domain Archaea, including those from the Crenarchaeota, Euryarchaeota and Thaumarchaeota (Figure 1b).…”
Section: Metagenome Assembliesmentioning
confidence: 99%
See 1 more Smart Citation
“…Archaea form biofilms within many microbial ecosystems such as acid mine drainage sites, seafloor sediments or acidic hot springs mats (Baker and Banfield, 2003;Orcutt et al, 2011); Kozubal et al, 2012). Initial description of the archaeal biofilms were reported in the euryarchaeota Archaeoglobus fulgidus (Lapaglia and Hartzell, 1997) and in the bi-species biofilm of Pyrococcus furiosus and Methanopyrus kandlerii (Schopf et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…High temperatures (480C), low pH (pHo3) conditions generally favor Archaea-dominated communities (Bolduc et al, 2012). Bacteria and eukaryotes are few or in many cases, absent (Reysenbach et al, 1994;Blank et al, 2002;Kozubal et al, 2012;Macur et al, 2012;Jay et al, 2013). These extreme environmental conditions favor not only the Archaea but also result in a relatively simplified microbial community structure.…”
Section: Introductionmentioning
confidence: 99%